(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
The ability to adjust to different life circumstances impacts one’s quality of life in any given period. This concept underscores one’s adversity quotient, which measures one’s ability to overcome these challenges and transform every problem into an opportunity for personal accomplishment. In light of this premise, this study aimed to determine the status of the life adjustments of the students and faculty of the School of Education, Arts, and Sciences (SEAS) of Union Christian College in the City of San Fernando, La Union, as the basis for the development of a psychosocial program. It utilized a descriptive research design, employing comparative and correlational techniques. SEAS students and faculty voluntarily participated in the study, indicating an effect size of 0.8; 85% achieved power with a 0.05 margin of error. The questionnaire was a modified adversity quotient scale by Stoltz with Tagalog translation adopted from the UCC-CRDEPS validated and pilot tested tool used in the Graduate School thesis. The data gathered were treated with descriptive and inferential statistics to yield appropriate analysis and interpretation. The researchers strictly observed the protocols of the study responsive to the ethical and responsible conduct of research in the College. The findings showed that the two groups of respondents registered below average in their general adversity quotient, average in Reach, and below average in Ownership, Control, and Endurance (lowest). Meanwhile, they have rated that the factors (personal, family, and social) highly affected their adversity quotients, personal being the highest and family the lowest. On the test of differences between the two groups of respondents, the results showed significantly better control of adversaries among the student-respondents than the faculty-respondents. Still, no significant difference existed between them in the other dimensions or their general AQ and the extent of the effect of the factors on their AQ. Furthermore, the identified factors did not significantly predict the respondents’ AQ. Based on the findings, the researchers concluded that both groups of respondents exhibited poor adjustments towards life adversaries, with the younger group, as represented by their roles (faculty or students), having better control of these occurrences; hence, the need for SEAS to develop psychosocial programs or strengthen any existing programs to promote better life adjustments among its students and faculty.